Developmental toxicity of cadmium in mice. I. Embryotoxic effects - Soukupová, D; Dostál, M (Functional and developmental morphology, 1991)
Embryotoxic effects of CdCl2 administered in a single dose of 2.0, 4.0 or 6.0 mg/kg body weight to randombred ICR mice (Velaz) on the 8th, 9th, 10th, 11th, 12th, 13th or 14th day of pregnancy were studied. The embryolethal effect, being highest after treatment with 6.0 mg/kg CdCl2 on the 12th and 13th day of pregnancy (50.0 and 61.3%) was not significantly correlated to the day of treatment. Among survivors, foetuses with haemorrhagic bullae, limb malformations, exencephaly, cleft palate, open eyelids and tail deformities occurred. Mainly the right-sided limbs were malformed. The administration of 2.0 and 4.0 mg/kg CdCl2 on the 10th day of pregnancy induced fore limb polydactylies, whereas with the dose of 6.0 mg also oligodactylies were induced. The foetal body weight was reduced only by a dose of 6.0 mg CdCl2 administered on the 12th day of pregnancy. Reduction of the thymus weight was a constant effect of treatment with the higher doses of cadmium from the 9th to the 14th day of pregnancy.
Keywords: Animals; Cadmium; myši inbrední ICR; Female; zvířata; Mice; Pregnancy; těhotenství; abnormality vyvolané léky; kadmium; Abnormalities, Drug-Induced; embryonální a fetální vývoj; Embryonic and Fetal Development; Mice, Inbred ICR; ženské pohlaví; myši